5.3.50 Problems 4901 to 5000

Table 5.383: Second order ode

#

ODE

Mathematica

Maple

15449

\[ {}y^{\prime \prime }+9 y = 54 x^{2} {\mathrm e}^{3 x} \]

15450

\[ {}y^{\prime \prime } = 6 x \,{\mathrm e}^{x} \sin \left (x \right ) \]

15451

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left (-6 x -8\right ) \cos \left (2 x \right )+\left (8 x -11\right ) \sin \left (2 x \right ) \]

15452

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left (12 x -4\right ) {\mathrm e}^{-5 x} \]

15453

\[ {}y^{\prime \prime }+9 y = 39 \,{\mathrm e}^{2 x} x \]

15454

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -3 \,{\mathrm e}^{-2 x} \]

15455

\[ {}y^{\prime \prime }+4 y^{\prime } = 20 \]

15456

\[ {}y^{\prime \prime }+4 y^{\prime } = x^{2} \]

15457

\[ {}y^{\prime \prime }+9 y = 3 \sin \left (3 x \right ) \]

15458

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 10 \,{\mathrm e}^{3 x} \]

15459

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = \left (72 x^{2}-1\right ) {\mathrm e}^{2 x} \]

15460

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 4 x \,{\mathrm e}^{6 x} \]

15461

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 6 \,{\mathrm e}^{5 x} \]

15462

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 6 \,{\mathrm e}^{-5 x} \]

15463

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 24 \sin \left (3 x \right ) \]

15464

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 8 \,{\mathrm e}^{-3 x} \]

15465

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15466

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{-x} \]

15467

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 100 \]

15468

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = {\mathrm e}^{-x} \]

15469

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 10 x^{2}+4 x +8 \]

15470

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15471

\[ {}y^{\prime \prime }+y = 6 \cos \left (x \right )-3 \sin \left (x \right ) \]

15472

\[ {}y^{\prime \prime }+y = 6 \cos \left (2 x \right )-3 \sin \left (2 x \right ) \]

15473

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = x^{3} {\mathrm e}^{-x} \sin \left (x \right ) \]

15474

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = x^{3} {\mathrm e}^{2 x} \sin \left (x \right ) \]

15475

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{-7 x}+2 \,{\mathrm e}^{-7 x} \]

15476

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} \]

15477

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 4 \,{\mathrm e}^{-8 x} \]

15478

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 4 \,{\mathrm e}^{3 x} \]

15479

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{3 x} \]

15480

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = \cos \left (2 x \right ) x^{2} \]

15481

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{3 x} \sin \left (2 x \right ) \]

15482

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = {\mathrm e}^{4 x} \sin \left (2 x \right ) \]

15483

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = {\mathrm e}^{2 x} \sin \left (4 x \right ) \]

15484

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = x^{3} \sin \left (4 x \right ) \]

15485

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 3 x^{2} {\mathrm e}^{5 x} \]

15486

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 3 x^{4} \]

15501

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 27 \,{\mathrm e}^{6 x}+25 \sin \left (6 x \right ) \]

15502

\[ {}y^{\prime \prime }+9 y = 25 x \cos \left (2 x \right )+3 \sin \left (3 x \right ) \]

15503

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 5 \sin \left (x \right )^{2} \]

15504

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 20 \sinh \left (x \right ) \]

15505

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+8 y = \frac {5}{x^{3}} \]

15506

\[ {}2 x^{2} y^{\prime \prime }-x y^{\prime }+y = \frac {50}{x^{3}} \]

15507

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = 85 \cos \left (2 \ln \left (x \right )\right ) \]

15508

\[ {}x^{2} y^{\prime \prime }-2 y = 15 \cos \left (3 \ln \left (x \right )\right )-10 \sin \left (3 \ln \left (x \right )\right ) \]

15509

\[ {}3 x^{2} y^{\prime \prime }-7 x y^{\prime }+3 y = 4 x^{3} \]

15510

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = \frac {10}{x} \]

15511

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 6 x^{3} \]

15512

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 64 \ln \left (x \right ) x^{2} \]

15513

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 3 \sqrt {x} \]

15514

\[ {}y^{\prime \prime }+y = \cot \left (x \right ) \]

15515

\[ {}y^{\prime \prime }+4 y = \csc \left (2 x \right ) \]

15516

\[ {}y^{\prime \prime }-7 y^{\prime }+10 y = 6 \,{\mathrm e}^{3 x} \]

15517

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \left (24 x^{2}+2\right ) {\mathrm e}^{2 x} \]

15518

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{-2 x}}{x^{2}+1} \]

15519

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = \sqrt {x} \]

15520

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 12 x^{3} \]

15521

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{2} \]

15522

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = \ln \left (x \right ) \]

15523

\[ {}x^{2} y^{\prime \prime }-2 y = \frac {1}{x -2} \]

15524

\[ {}x y^{\prime \prime }-y^{\prime }-4 x^{3} y = x^{3} {\mathrm e}^{x^{2}} \]

15525

\[ {}x y^{\prime \prime }+\left (2+2 x \right ) y^{\prime }+2 y = 8 \,{\mathrm e}^{2 x} \]

15526

\[ {}\left (1+x \right ) y^{\prime \prime }+x y^{\prime }-y = \left (1+x \right )^{2} \]

15527

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }-4 y = \frac {10}{x} \]

15528

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 12 \,{\mathrm e}^{2 x} \]

15535

\[ {}y^{\prime \prime }+36 y = 0 \]

15536

\[ {}y^{\prime \prime }-12 y^{\prime }+36 y = 0 \]

15537

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

15538

\[ {}y^{\prime \prime }-36 y = 0 \]

15539

\[ {}y^{\prime \prime }-9 y^{\prime }+14 y = 0 \]

15540

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+16 y = 0 \]

15541

\[ {}2 x y^{\prime \prime }+y^{\prime } = \sqrt {x} \]

15543

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

15544

\[ {}y^{\prime \prime }+3 y = 0 \]

15545

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+9 y = 0 \]

15546

\[ {}x^{2} y^{\prime \prime }+\frac {5 y}{2} = 0 \]

15548

\[ {}x^{2} y^{\prime \prime }-6 y = 0 \]

15549

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

15550

\[ {}y^{\prime \prime } = {y^{\prime }}^{2} \]

15551

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0 \]

15552

\[ {}y^{\prime \prime }-8 y^{\prime }+25 y = 0 \]

15553

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-30 y = 0 \]

15554

\[ {}y^{\prime \prime }+y^{\prime }-30 y = 0 \]

15555

\[ {}16 y^{\prime \prime }-8 y^{\prime }+y = 0 \]

15556

\[ {}4 x^{2} y^{\prime \prime }+8 x y^{\prime }+y = 0 \]

15558

\[ {}2 x^{2} y^{\prime \prime }-3 x y^{\prime }+2 y = 0 \]

15559

\[ {}9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = 0 \]

15561

\[ {}2 y^{\prime \prime }-7 y^{\prime }+3 = 0 \]

15562

\[ {}y^{\prime \prime }+20 y^{\prime }+100 y = 0 \]

15563

\[ {}x y^{\prime \prime } = 3 y^{\prime } \]

15564

\[ {}y^{\prime \prime }-5 y^{\prime } = 0 \]

15565

\[ {}y^{\prime \prime }-9 y^{\prime }+14 y = 98 x^{2} \]

15566

\[ {}y^{\prime \prime }-12 y^{\prime }+36 y = 25 \sin \left (3 x \right ) \]

15567

\[ {}y^{\prime \prime }-9 y^{\prime }+14 y = 576 x^{2} {\mathrm e}^{-x} \]

15568

\[ {}y^{\prime \prime }-12 y^{\prime }+36 y = 81 \,{\mathrm e}^{3 x} \]

15569

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 3 \sqrt {x} \]

15570

\[ {}y^{\prime \prime }-12 y^{\prime }+36 y = 3 x \,{\mathrm e}^{6 x}-2 \,{\mathrm e}^{6 x} \]

15571

\[ {}y^{\prime \prime }+36 y = 6 \sec \left (6 x \right ) \]

15572

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 18 \ln \left (x \right ) \]